CAD‐based hardware attenuation correction in PET/MRI: First methodical investigations and clinical application of a 16‐channel RF breast coil. Issue 11 (27th October 2021) - Lindemann, Maike E.; Oehmigen, Mark; Lanz, Titus; Grafe, Hong; Bruckmann, Nils Martin; Umutlu, Lale; Quick, Harald H.
Abstract: Purpose: Aim of this study was to evaluate the use of computer‐aided design (CAD) models for attenuation correction (AC) of hardware components in positron emission tomography/magnetic resonance (PET/MR) imaging. Methods: The technical feasibility and quantitative impact of CAD‐AC compared to computer tomography (CT)‐based AC (reference) was investigated on a modular phantom consisting of 19 different material samples (plastics and metals arranged around a cylindrical emission phantom) typically used in phantoms, patient tables, and radiofrequency (RF) coils in PET/MR. The clinical applicability of the CAD‐AC method was then evaluated on a 16‐channel RF breast coil in a PET/MR patient study. The RF breast coil in this study was specifically designed PET compatible. Using this RF breast coil, the impact on clinical PET/MR breast imaging was systematically evaluated in breast phantom measurements and, furthermore, in n = 10 PET/MR patients with breast cancer. PET data were reconstructed three times: (1) no AC (NAC), (2) established CT‐AC, and (3) CAD‐AC. For both phantom measurements, a scan without attenuating hardware components (material probes or RF breast coil) was acquired serving as reference. Relative differences in PET data were calculated for all experiments. Results: In all phantom and patient measurements, significant gains in PET signal compared to NAC data were measurable with CT and CAD‐AC. In initial phantom experiments, mean relative differences of –0.2% for CT‐AC and 0.2% for CAD‐AC were calculated compared to reference measurements without the material probes. The application to a RF breast coil depicts that CAD‐AC results in significant gains compared to NAC data (10%) and a slight underestimation in PET signal of –1.3% in comparison to the no‐coil reference measurement. In the patient study, a total of 15 congruent lesions in all 10 patients with a mean relative difference of 14% (CT and CAD‐AC) in standardized uptake value compared to NAC data could be detected. Conclusions: To ensure best possible PET image quality and accurate PET quantification in PET/MR imaging, the AC of hardware components such as phantoms and RF coils is important. In initial phantom experiments and in clinical application to an RF breast coil, it was found that CAD‐based AC results in significant gains in PET signal compared to NAC data and provides comparably good results to the established method of CT‐based AC.